2022
DOI: 10.1007/s11064-022-03742-6
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Manipulating Microglia to Determine Their Role in the Healthy and Diseased Brain

Abstract: Microglia are the specialized macrophages of the central nervous system and play an important role in neural circuit development, modulating neurotransmission, and maintaining brain homeostasis. Microglia in normal brain is quiescent and show ramified morphology with numerous branching processes. They constantly survey their surrounding microenvironment through the extension and retraction of their processes and interact with neurons, astrocytes, and blood vessels using these processes. Microglia respond quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 144 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…In two-photon microscopy-based time-lapse imaging recordings, it was found that microglia directly contact astrocytes by extending their branches toward the astrocytes ( 161 ). When the brain microenvironment is disrupted, microglia/macrophages and astrocytes play important roles in various pathological states such as IS ( 162 164 ). Among them, modulators such as IL-1β, TNF-α, TGF-β, adenosine, ATP and glutamate contribute to functional communication between microglia/macrophages and astrocytes ( 165 168 ), which is critical for immune responses in the brain ( 163 ).…”
Section: Mechanisms Of Microglia/macrophages In Ismentioning
confidence: 99%
“…In two-photon microscopy-based time-lapse imaging recordings, it was found that microglia directly contact astrocytes by extending their branches toward the astrocytes ( 161 ). When the brain microenvironment is disrupted, microglia/macrophages and astrocytes play important roles in various pathological states such as IS ( 162 164 ). Among them, modulators such as IL-1β, TNF-α, TGF-β, adenosine, ATP and glutamate contribute to functional communication between microglia/macrophages and astrocytes ( 165 168 ), which is critical for immune responses in the brain ( 163 ).…”
Section: Mechanisms Of Microglia/macrophages In Ismentioning
confidence: 99%
“…A pathological brain [14][15][16] refers to a brain that exhibits abnormal structural or functional changes often associated with various neurological, neurodegenerative, or psychiatric disorders [17]. These alterations can result from a wide range of conditions, including tumors [18], infections [19], traumatic injuries [20], neurodegenerative diseases like Alzheimer's [21] or Parkinson's [22], and mental health disorders like depression [23] or schizophrenia [24].…”
Section: Introductionmentioning
confidence: 99%